Contributory aspects of the company to the quality of life of workers; a sustainable social vision. (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2012)
This article generated from research, emphasizes the hermeneutical experience on tax aspects of the company to the quality of life of workers under a sustainable social vision. The dimensionalities associated with quality of life, and were taken from Manzilla Figallo (2004), announcing contributions to health, nutrition, rest and recreation, housing, clothing, income, career development, personal safety, self-realization, social protection, education, relationships, self-confidence, sexuality, spirituality, art and culture, environment and civic participation. The methodological condition manifested as now constituted a human relationship within which communication-relationship between the researcher and the subjects, formed an essential element in the dialogue appellant seeking to access through direct interview to seven (7) employees and three (3) business managers Cocuy Leal (Leal and Successor CIA Ramon, CA), Barquisimeto, Lara State. For purposes of this article, we took only the categories and subcategories emerging from the social actor's voice 1. As finding the scene of the quality of life, the subcategories were identified: promotion and collective vision of health, self-confidence and commitment to the work, which is characteristic of the company's philanthropy to the worker within a temporal link volunteer also limited attention to communities. As reflection is assumed metaphor: like waves in the sea, realizing that the light generated by the network of meanings associated with a better business community must be transparent in its shades of action.
Keywords: tax aspects of the company; quality of life; sustainable social vision